Exploring Global Trends and Innovations in Educational Technology: A Bibliometric Analysis of Emerging Paradigms and Key Contributions - Tua, Sahat (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This study aims to investigate the latest trends in educational technology and identify emerging innovations in the scientific literature using the Bibliometric Analysis method. The background of the research confirms the importance of an in-depth understanding of the latest developments in technology-based education, given the rapid changes taking place in this domain. The results highlight the significant influence of countries such as the United States, Russia, Brazil, and China in initiating and realizing educational technology innovations. In addition, the study identified several significant journals, such as